The use of fermented pellet concentrate from commercial feed, sago waste, and other local feedstuffs on the performance of grower pigs in Yapen Islands - Herry H. Auparay; Onesimus Yoku; Sangle Y. Randa (Fakultas Peternakan Universitas Papua, 2026)
The growth and productivity of pigs are significantly influenced by the quality and adequacy of nutritional intake, especially feed that meets their physiological needs. This study aimed to evaluate the performance of grower pigs fed rations supplemented with fermented pellet concentrate made from commercial feed (concentrate 511), sago waste, tofu waste, sweet potato leaves, corn and coconut residue. The research was conducted over two months in 2024 in the Yapen Islands, involving 12 pigs aged 3–4 months. A randomized block design (RBD) was used with four treatments and three replications, grouped based on initial body weight. The treatments were: P0 = 100% basal ration (no concentrate), P1 = 95% basal ration + 5% fermented concentrate, P2 = 90% basal ration + 10% fermented concentrate, and P3 = 85% basal ration + 15% fermented concentrate. Observed variables included feed intake, daily weight gain, and feed conversion ratio. The results showed that the addition of fermented pellet concentrate significantly affected (P<0.05) the daily weight gain of grower pigs but had no significant effect on feed intake, dry matter intake, or feed efficiency. The best performance was observed in P3 (15% fermented concentrate + 85% basal ration), which resulted in the most optimal growth response